"Looking out for each other": a qualitative study on the role of social network interactions in asthma management among adult Latino patients presenting to an emergency department. (September 2014) - Pai, Sucheta; Boutin-Foster, Carla; Mancuso, Carol A.; Loganathan, Raghu; Basir, Riyad; Kanna, Balavenkatesh
Abstract Objective: The objective of this study was to identify the types of interactions between asthma patients and their social networks such as close family and friends that influence the management of asthma. Methods: Participants were Latino adults presenting for a repeat visit to the emergency department for asthma treatment. Qualitative interviews were conducted with 76 participants. They were asked to describe the experiences of their social networks that have asthma and how interactions with these individuals influenced their own asthma management. Responses were transcribed and analyzed using Grounded Theory as a qualitative analytic approach. Responses were assigned codes; similar codes were grouped into concepts and then categorized to form overarching themes. Results: Four themes emerged: (1) Perceptions of severity of asthma may be based on the experiences of social networks; (2) Economic factors may contribute to the sharing and borrowing of asthma medications between patients and their social networks; (3) Economic factors may contribute to using home remedies instead of prescribed medications; (4) Social network members may be unaware of the factors that trigger asthma and therefore, contribute to asthma exacerbations. Conclusion: This study identified important social network interactions that may impact asthma management in Latino adults. These results can be used to broaden the current focus of asthma self-management programs to incorporate discussions on the role of social networks. A focus on social network interactions addresses the social epidemiology of asthma and advances our understanding of root causes that may underlie the high prevalence of asthma in many Latino communities.